Penggunaan Aplikasi Pembelajaran Interaktif dalam Meningkatkan Keterampilan Dasar Siswa Sekolah Dasar di UPTD SD Negeri Dlambah Laok 2 Tanah Merah - Mulyadi, Ariep; Kusmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2024)
This study aims to explore the use of interactive learning applications in enhancing students' basic skills at UPTD SD Negeri Dlambah Laok 2, Tanah Merah District. The research method used is qualitative with a descriptive approach. The research subjects consisted of 30 students from grades IV and V and 5 subject teachers. Data collection was carried out through questionnaires, basic skills tests, and interviews. The results of the study indicate that the use of interactive learning applications significantly contributes to increasing student learning motivation, with 80% of students reporting improved interest and participation in learning. The average score for students' basic skills increased by 15% after 6 weeks of using the application. However, challenges such as limited technological infrastructure and the need for teacher training need to be addressed. This study provides important implications for the development of learning media in elementary schools and encourages the utilization of technology in education to create a more interactive and enjoyable learning environment.